EFFECT OF PROFITABILITY, LEVERAGE, AND FIXED ASSET INTENSITY ON TAX AVOIDANCE - Ikeu Ageng Aprianti; Daeng M. Nazier; Indah Umiyati (Journal of Taxation Analysis and Review, 2024)
The Malaysian Tax Authority, LHDN has identified 31,598 entities that have not reported their income and are undertaking tax evasion efforts. LHDN said the entities suspected of evading taxes consisted of individuals, businesses, companies, and others. Tax avoidance activities, especially aggressive ones, certainly erode the tax base and reduce potential state revenues. This situation arises because of the high dependence on tax revenues. With this research, it is hoped that companies will be more aware of paying taxes honestly. will examine the effect of profitability, leverage, and fixed asset intensity on tax avoidance in Malaysia. This study conducted a research method using quantitative methods. According to Sugiyono (2016: 8) the quantitative method is a research method based on the philosophy of positivism, used in researching certain populations or samples, collecting data using research instruments, data analysis is quantitative/statistical, the purpose of which is to prove the established hypothesis. Based on the results of research on the effect of Profitability (Return on Assets) on Tax Avoidance, it shows that there is no influence between Profitability on tax avoidance. The results of the Leverage Test on Tax Avoidance state that there is an influence between Leverage and tax avoidance. the results of the fixed asset intensity test stated that there was an influence between the Fixed Asset Intensity on tax evasion. Profitability has no effect on tax avoidance, meaning that changes in the value of profitability in the study period have no effect on tax evasion in companies. Leverage affects Tax Avoidance, meaning that changes in the value of Leverage (Debt to equity ratio) in the study period affect tax avoidance in companies. Fixed Asset Intensity has an effect on Tax Avoidance, meaning that changes in the value of fixed asset intensity in the study period have an effect on tax avoidance in companies